2011
DOI: 10.1051/0004-6361/201116693
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared properties of nearby low-luminosity AGN at high angular resolution

Abstract: We present high spatial resolution mid-infrared (MIR) 12 μm continuum imaging of low-luminosity active galactic nuclei (LLAGN) obtained with VLT/VISIR. Our goal is to determine whether the nuclear MIR emission of LLAGN is consistent with the existence of a dusty obscuring torus, the key component of the unification model for AGN. Based on available hard X-ray luminosities and the previously known tight correlation between the hard X-ray and 12 μm luminosities, we selected a sample of 17 nearby LLAGN without av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
117
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 145 publications
(209 reference statements)
23
117
6
Order By: Relevance
“…4.1), resulting in high completeness levels. With decreasing redshifts, however, X-ray observations and optical spectroscopy are able to detect more low-luminosity AGN, sources that will probably not dominate the total IR SED of a galaxy, resulting either from IR-luminous obscured starformation in the galaxy (Rigopoulou et al 1999;Veilleux et al 2009;Nordon et al 2013) or from the complete absence of a dust torus (e.g., Ho 2008;Asmus et al 2011;Burlon et al 2011;Plotkin et al 2012). The former plays a significant role, since IR-selected AGN have mostly been found in star-forming hosts (Hickox et al 2009;Griffith & Stern 2010).…”
Section: Discussion On Agn Ir-selection Completenessmentioning
confidence: 99%
See 2 more Smart Citations
“…4.1), resulting in high completeness levels. With decreasing redshifts, however, X-ray observations and optical spectroscopy are able to detect more low-luminosity AGN, sources that will probably not dominate the total IR SED of a galaxy, resulting either from IR-luminous obscured starformation in the galaxy (Rigopoulou et al 1999;Veilleux et al 2009;Nordon et al 2013) or from the complete absence of a dust torus (e.g., Ho 2008;Asmus et al 2011;Burlon et al 2011;Plotkin et al 2012). The former plays a significant role, since IR-selected AGN have mostly been found in star-forming hosts (Hickox et al 2009;Griffith & Stern 2010).…”
Section: Discussion On Agn Ir-selection Completenessmentioning
confidence: 99%
“…These findings imply that dust-free clouds at <R sub frequently represent the bulk of the X-ray obscuration. As such, the AGN-induced dust emission will be relatively weak or non-existent especially in lowluminosity AGN (Ho 2008;Asmus et al 2011;Plotkin et al 2012), but high-luminosity cases also exist where the IR excess is not as extreme as expected (Comastri et al 2011). …”
Section: Discussion On Agn Ir-selection Completenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendoza-Castrejón et al 2015). Subarcsecond resolution studies claim a tight correlation between rest frame luminosities νL ν (12 µm) and L X (2−10 keV) for Type-1 and Type-2 Seyferts Gandhi et al 2009;Asmus et al 2011;Masegosa et al 2013;González-Martín et al 2013). Imaging data at mid-IR wavelengths have shown that some Compton-thick LINER candidates might fall off this relation, with L 12 µm higher than expected for their L X (Mason et al 2012;Masegosa et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Nowadays we know that around 75−90% of LINERs show evidence of AGNs using multi-wavelength information (González-Martín et al 2006, 2009aDudik et al 2009;Younes et al 2011;Asmus et al 2011;Mason et al 2012) 1 . This is also confirmed from X-ray and UV variability studies (Maoz et al 2005;Hernández-García et al 2013.…”
Section: Introductionmentioning
confidence: 99%